Development of user-friendly simple statistical software: Linear regression analysis series - Hari Purnomo Susanto; Ika Noviantari; Nely Indra Meifiani; Mega Isvanidiana Purnamasari; Tika Dedy Prasetyo; Mobinta Kusuma; Sumin Sumin (Psychology, Evaluation, and Technology in Educational Research, 2025)
Regression analysis is a statistical technique frequently employed across diverse disciplines utilizing SPSS. Users lacking a robust basis in regression and infrequently utilizing SPSS will experience anxiety. Anxiety will be intensified by the interpretation of the analysis results. This work aims to create user-friendly statistical software for regression analysis, requiring little configuration and capable of interpreting analytical results. This study employed the SCLD development model. This paradigm comprises five stages: Planning, Analysis, Design, Implementation, and System. The produced software is titled Simple Statistical Software series Regression Analysis, abbreviated as 3S-AR. The development yielded the 3S-AR program, which possesses functionality for regression analysis. The validation of development results was conducted by comparing the outcomes of 3S-AR analysis with those obtained from SPSS software. 3S-AR provides numerous advantages. Initially, it was user-friendly, and minimal configuration was required. A single analysis can present the outcomes of the regression analysis alongside all relevant assumptions. Secondly, the capability to offer an interpretation of the analytical findings. Third, if an analysis is incomplete, it can offer recommendations on the user's next steps. Fourth, it is complimentary. The development outcomes can facilitate users in conducting regression analysis with ease, particularly for individuals lacking a robust statistical background and proficiency in regression analysis tools.